2018
DOI: 10.1155/2018/3472471
|View full text |Cite
|
Sign up to set email alerts
|

Hysterectomy with Bilateral Salpingo-Oophorectomy in Female-to-Male Gender Affirmation Surgery: Comparison of Two Methods

Abstract: Introduction The optimal route for hysterectomy with bilateral salpingo-oophorectomy in female-to-male gender affirmation surgery is still under debate, due to the quite limited and inconsistent published data. The aim of this study is to present and compare the results of vaginal and laparoscopic hysterectomy as part of gender affirmation surgery in female-to-male transsexuals. Materials and Methods Between 2012 and 2017, 124 female-to-male transsexuals, aged 18–43 years (mean age: 28.5), underwent hysterecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Ring metoidioplasty combines the previous steps with that of urethral elongation. The ring flap elongates the urethra by using an anterior vaginal wall flap in conjunction with labia minora flaps [7,13] . The Belgrade metoidioplasty technique follows concepts and techniques used in hypospadias repair [14] .…”
Section: Metoidioplasty Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…Ring metoidioplasty combines the previous steps with that of urethral elongation. The ring flap elongates the urethra by using an anterior vaginal wall flap in conjunction with labia minora flaps [7,13] . The Belgrade metoidioplasty technique follows concepts and techniques used in hypospadias repair [14] .…”
Section: Metoidioplasty Techniquesmentioning
confidence: 99%
“…In their 2019 series of 593 patients undergoing one-stage Belgrade metoidioplasty, Djordjevic et al reported stricture and fistula rates of 2% (n = 10) and 8% (n = 48), respectively; all cases required surgical revision [7] . Lin-Brande et al [12] , 2020 33 ± UL 0 0 4 (2 from each group)…”
Section: Urinary Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sequencing of hysterectomy, salpingo-oophorectomy, and vaginectomy can vary. Hysterectomy and salpingo-oophorectomy are commonly performed using a transvaginal or standard laparoscopic approach during a separate stage in advance of masculinizing genital surgical procedures [13] . A primary advantage of this staging is to avoid the longer operative times, increased procedural blood loss, and greater physiologic disturbance when combining these with other procedures [14] .…”
Section: Hysterectomy Salpingo-oophorectomy Vaginectomymentioning
confidence: 99%
“…Chest masculinization and removal of female organs are often required by transgender men and gender non-conforming individuals as a first step of gender affirming surgery. All routes of hysterectomy are feasible and safe when performed for gender affirmation, with no documented increased risk of complications compared to the cisgender population and are associated with an improved quality of life [ 3 , 4 , 5 , 6 ]. Minimally invasive approaches are the most common (laparoscopy, vaginal, laparoscopic-assisted vaginal, and robot-assisted laparoscopic route), each with particular benefits for transmen in terms of scarring, hospitalization time, and conservation of vasculature for potential future gender affirming surgeries [ 3 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%